A Ni-MOF derived graphene oxide combined Ni3S2–Ni/C composite and its use in the separator coating for lithium sulfur batteries. Issue 7 (1st February 2023) - Qian, Xinye; Cheng, Jian; Wang, Yuhe; Jin, Lina; Chen, Jianyu; Hao, Qingyuan; Zhang, Ke
Abstract : A Ni3 S2 –Ni@C(GO) composite was prepared by high temperature carbonization from Ni-MOF, and was coated on a PE film to use it as a Li–S battery separator. The Ni3 S2 –Ni@C(GO) composite has physical confinement and shows a catalytic effect on lithium polysulfides. Abstract : Lithium–sulfur batteries (LSBs) are widely regarded as reliable novel secondary batteries due to their low price and high capacity. Nevertheless, the notorious "shuttle effect" limits the commercialization of LSBs. In order to solve this problem, we fabricated a Ni3 S2 –Ni/C composite through carbonization, vulcanization and hydrothermal reactions by using a Ni-MOF precursor and applied it as a separator modification layer to enhance the electrochemical properties of LSBs. To further increase the conductivity of the material, a small amount of GO was added during the experiment. The prepared material was also used as separator modified coating material to optimize the electrochemical performance of LSBs. The as prepared Ni3 S2 –Ni/C(GO) composite shows good conductivity and has a superior porous structure and abundant active sites. Lithium polysulfides (LPs) can be physically confined and chemically adsorbed, what is more, the Ni and Ni3 S2 active sites enable fast conversion of LPs which further optimizes the rate performance. From the cycle performance measurement, the initial discharge specific capacity of the Ni3 S2 –Ni/C(GO) modified separator battery is found to be 1263.4, 1181.5, 1090.6, and 840.3 mA h g −1 at 0.05, 0.1, 0.3 and 0.5C, respectively. After 400 charge/discharge cycles at 0.5C, the capacity remains at 483.6mA h g −1 with a capacity retention ratio of 57.56%.